2015
DOI: 10.1016/j.sjbs.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Conocarpus biochar as a soil amendment for reducing heavy metal availability and uptake by maize plants

Abstract: The objective of this study was to assess the use of Concarpus biochar as a soil amendment for reducing heavy metal accessibility and uptake by maize plants (Zea mays L.). The impacts of biochar rates (0.0, 1.0, 3.0, and 5.0% w/w) and two soil moisture levels (75% and 100% of field capacity, FC) on immobilization and availability of Fe, Mn, Zn, Cd, Cu and Pb to maize plants as well as its application effects on soil pH, EC, bulk density, and moisture content were evaluated using heavy metal-contaminated soil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(85 citation statements)
references
References 42 publications
10
72
2
1
Order By: Relevance
“…Undoubtedly, the considerable increase in soil pH as a result of application of organic materials (especially biochars) contributed to this. The obtained research results on the decrease in Mn mobility find confirmation in the results published by Al-Wabel et al (2015). Reduction of acidification led to formation of poorly soluble Mn compounds in the soil.…”
Section: Content Of Fe and Mn In Mobile Forms And In Om-bound Formssupporting
confidence: 85%
See 2 more Smart Citations
“…Undoubtedly, the considerable increase in soil pH as a result of application of organic materials (especially biochars) contributed to this. The obtained research results on the decrease in Mn mobility find confirmation in the results published by Al-Wabel et al (2015). Reduction of acidification led to formation of poorly soluble Mn compounds in the soil.…”
Section: Content Of Fe and Mn In Mobile Forms And In Om-bound Formssupporting
confidence: 85%
“…It has been shown that the content of Fe and Mn extracted with 0.025 M C 10H22N4O8 was higher than the content of these elements extracted with 1 M NH4NO3, mainly due to different extraction force of the solutions (Al-Wabel et al, 2015). The obtained results indicate that the amendment of organic materials to the soil did not have much effect on the content of Fe and Mn in the organic fraction (Table 6).…”
Section: Content Of Fe and Mn In Mobile Forms And In Om-bound Formsmentioning
confidence: 84%
See 1 more Smart Citation
“…The root uptake of Zn, Pb, Cd and Cu was reduced by as much as 19%, 30%, 50 and 28%, respectively, in T4 in the case of FC soil and 13%, 14%, 19 and 32%, respectively, in TG soil compared to their respective controls. Similarly, 28, 60 and 53.2% reductions in Zn, Cu and Cd, respectively were reported after 10% biochar application to soil 24 . These results further illustrated that the reduction in the bioavailable fraction in FC and TG soil decreased the uptake of HMs in Brassica roots.
Figure 4Effect of bamboo biochar on root uptake (mg kg −1 DW) of TEs in Brassica juncea .
…”
Section: Resultsmentioning
confidence: 69%
“…Biochar is a carbon rich, porous, purpose-produced charcoal manufactured during the pyrolysis of organic residues such as municipal waste, animal wastes, wood, crop residues, and biosolids. Several studies revealed that addition of biochars to soil greatly enhanced the sorption of heavy metal(loid)s and significantly reduced their mobility and phytoavailability (Al-Wabel et al, 2015;Puga et al, 2015). Addition of biochar to soil changes chemical, physical, and biological properties of soil.…”
Section: Immobilization Techniquesmentioning
confidence: 99%